(untitled) (Journal of Applied Learning and Teaching, 2020)
Nursing is a competence-based profession, and clinical competence has been widely discussed within the nursing literature over the past three decades due to growing public demand for professional accountability. However, the concept remains nebulous and defined differently by healthcare researchers. This paper presents a concept analysis which reviews the different competence-based frameworks and its application within the nursing literature. The analysis reveals flaws in the existing assessment methods used by current nursing regulatory bodies for their licensure system and proposes a modified Miller’s model for utilisation in nursing education.